Simplified hysteretic model for the representation of the biaxial bending response of RC columns - Rodrigues, H.
The biaxial cyclic behaviour of reinforced concrete columns has been object of many experimental studies over the past years, and different modelling strategies have been proposed. In the present paper, a simplified hysteretic model is proposed for the representation of the non-linear response of reinforced concrete members subjected to biaxial bending combined with a constant axial load. The proposed model corresponds to an upgrade of an existing uniaxial hysteretic model, with piecewise linear behaviour, and adopts an interaction function based on the formulation of Bouc–Wen smooth hysteretic model. The proposed biaxial model requires the same type of information as the corresponding uniaxial model, and in order to couple the two loading directions a correcting term is applied to the response in each uniaxial direction. For the calibration of the proposed interaction function, optimisation techniques were used to adjust the required parameters. Finally, the validity of the simplified model is demonstrated through the simulation of the response of reinforced concrete columns tested under biaxial loading.